You are on page 1of 1

# Taylor series expansions of common functions

Function

Kowalski

Taylor series: [long hand]

[Σ notation]

=

X
f (n) (c)
(x − c)n
n!
n=0

R

=

X
1 n
x
n!
n=0

1 3
1
1
1
1 11
x + x5 − x7 + x9 −
x + ···
3!
5!
7!
9!
11!

=

X
(−1)n 2n+1
x
(2n + 1)!
n=0

1 2
1
1
1
1 10
x + x4 − x6 + x8 −
x + ···
2!
4!
6!
8!
10!

=

X
(−1)n 2n
x
(2n)!
n=0

f 0 (c)
f 00 (c)
(x − c) +
(x − c)2 + · · ·
1
2!

f (x)

=

f (c) +

x

e

=

1
1
1
1
1
1 + x + x2 + x3 + x4 + x5 + · · ·
1!
2!
3!
4!
5!

sin(x)

=

x−

cos(x)

=

1−

1
1−x

=

xp

=

1+

ln(x)

=

1
1
1
1(x − 1) − (x − 1)2 + (x − 1)3 − (x − 1)4 + · · ·
2
3
4

=

X
(−1)n+1
(x − 1)n
n
n=1

1

arctan(x)

=

1
1
1
1
1
x − x3 + x5 − x7 + x9 − x11 + · · ·
3
5
7
9
11

=

X
(−1)n 2n+1
x
2n + 1
n=0

1

2

3

4

5

6

7

1 + x + x + x + x + x + x + x + ···

=

X

xn

1

n=0

p
p(p − 1)
p(p − 1)(p − 2)
(x − 1) +
(x − 1)2 +
(x − 1)3 + · · · =
1!
2!
3!

* If p is not a positive number. If p is a positive integer, then R = ∞.

X
p(p − 1) · · · (p − n + 1)
(x − 1)n
n!
n=0

1∗